2020
DOI: 10.1093/trstmh/traa089
|View full text |Cite
|
Sign up to set email alerts
|

‘Far from the views of decision-makers’: podoconiosis instruction at medical schools across endemic countries in Africa

Abstract: Background Podoconiosis is a neglected tropical disease that causes significant physical, emotional and financial suffering, especially among impoverished rural farmers. Sufficient physician training is integral to optimizing patient outcomes through timely diagnosis and appropriate management. Therefore we sought to characterize podoconiosis instruction offered to medical students in endemic African countries. Methods We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…This is similar to a recent Rwandan study which demonstrated poor knowledge around podoconiosis as well as minimal clinical experience in treating affected persons [26]; this was compounded by shortages of supplies and drugs as in our study. Another recent study which explored the inclusion of podoconiosis in medical undergraduate studies across all endemic countries in Africa found there was insufficient specific teaching on podoconiosis [27], mirroring our respondents, along with earlier Ethiopiaspecific reports [28] of high levels of misconceptions among health care professionals. Education interventions targeted to healthcare workers in endemic areas should be a component of any planned intervention to aid success.…”
Section: Is It Feasible?supporting
confidence: 72%
“…This is similar to a recent Rwandan study which demonstrated poor knowledge around podoconiosis as well as minimal clinical experience in treating affected persons [26]; this was compounded by shortages of supplies and drugs as in our study. Another recent study which explored the inclusion of podoconiosis in medical undergraduate studies across all endemic countries in Africa found there was insufficient specific teaching on podoconiosis [27], mirroring our respondents, along with earlier Ethiopiaspecific reports [28] of high levels of misconceptions among health care professionals. Education interventions targeted to healthcare workers in endemic areas should be a component of any planned intervention to aid success.…”
Section: Is It Feasible?supporting
confidence: 72%
“…Our findings align with previous studies from Rwanda and Ethiopia demonstrating that health workers lacked the specific knowledge to effectively treat and care for podoconiosis patients [ 19 21 , 34 ]. Similar misperceptions on disease cause and management were documented among medical faculty in endemic Sub-Saharan countries [ 23 ]. Altogether, this highlights a shared need for podoconiosis education for nurses and physicians to accelerate early detection, reduce patient stigma, improve prevention, and optimize patient outcomes.…”
Section: Discussionmentioning
confidence: 56%
“…Survey questions were initially developed by this team to assess podoconiosis instruction at African medical schools and were modified for nursing schools [ 23 ]. The survey tool was developed in English, pre-tested on 14 nursing tutors and lecturers in East Africa, and adapted as necessary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of a seamless interchange between research and education has been demonstrated regarding the serious but neglected tropical disease, podoconiosis (a type of tropical lymphoedema). Research has identified important gaps in knowledge by health workers as well as insufficiencies in medical school training (Bayisenge et al, 2020 ; Fowler et al, 2020 ). Importantly, new knowledge has been generated regarding the demographic profile of podoconiosis patients (Bikorimana et al, 2020 ), which could inform the development of programs of training and instruction to ensure that training is based on evidence that is current and high-quality thereby helping to reduce inequities in service provision for under-represented diseases.…”
Section: Foundational Research Questionsmentioning
confidence: 99%